2015
DOI: 10.1111/jbi.12548
|View full text |Cite
|
Sign up to set email alerts
|

Unforeseen biogeographical patterns in a multiple parasite system in Macaronesia

Abstract: Aim Understanding the reasons why hosts lose, maintain or swap their parasite burden after colonizing new areas has long intrigued island biogeographers. Using molecular markers, we evaluated parasite biogeography of a multiple parasite system of Apicomplexa protozoans (haemosporidian and coccidian parasites) showing different modes of transmission in the spectacled warbler (Sylvia conspicillata), a small passerine with recently founded populations in Macaronesia.Location Twelve oceanic islands of three Macaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 55 publications
1
31
0
7
Order By: Relevance
“…As generalist parasites are considered poor competitors (Hellgren et al , 2009), an increase of co-infections on islands could play a role in limiting parasite densities and prevalence. Previous studies on the prevalence of blood parasites on islands were inconclusive, with either higher (Illera et al , 2015) or lower prevalence on islands (Pérez-Rodríguez et al , 2013). These conflicting results may arise from the fact that parasite prevalence is also likely to vary in relation to environmental and local factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As generalist parasites are considered poor competitors (Hellgren et al , 2009), an increase of co-infections on islands could play a role in limiting parasite densities and prevalence. Previous studies on the prevalence of blood parasites on islands were inconclusive, with either higher (Illera et al , 2015) or lower prevalence on islands (Pérez-Rodríguez et al , 2013). These conflicting results may arise from the fact that parasite prevalence is also likely to vary in relation to environmental and local factors.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it remains uncertain if and how these patterns described for insular vertebrates apply to their parasite fauna (Illera et al , 2015; Jean et al , 2016). Although island biogeography of parasites and their colonization histories have received increasing attention in recent years (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have explored the LDG within a host species, and even fewer have used a globally-distributed species, as recommended by Poulin (2014). Illera et al (2015) failed to find a significant relationship between latitude and richness of three genera of haematozoa and coccidians in spectacled warblers in Macaronesia. Calvete et al (2003) found an inverse relationship between species diversity and latitude in their investigation of helminth communities of a partridge species in Spain, with higher diversity at lower latitudes (although the study area covered approximately six degrees in latitude).…”
Section: A Review Of Past Studies On the Latitudinal Diversity Pattermentioning
confidence: 99%
“…Islands are excellent environments for investigating pathogen-mediated selection. In line with island biogeography theory (MacArthur & Wilson, 1967), pathogen diversity and abundance are often lower on islands compared with the mainland, simplifying the study of host-pathogen interactions (Pérez-Rodríguez, Ramírez, Richardson, & Pérez-Tris, 2013;Clark, Clegg, & Lima, 2014; but see Illera, Fernández-Álvarez, Hernández-Flores, & Foronda, 2015).…”
Section: Introductionmentioning
confidence: 99%